Degenerative Changes in the Cervical Spine Are More Common in Middle-Aged Individuals with Thalidomide Embryopathy than in Healthy Controls - Ghassemi Jahani, Shadi A.; Danielsson, Aina; Ab-Fawaz, Rana; Hebelka, Hanna; Danielson, Barbro; Brisby, Helena (PloS one, 2016)
Thalidomide was used as a sedative drug for pregnant women in the 1950-60:s and resulted in children born with thalidomide embryopathy (TE), including upper limb malformations. These may alter the motion pattern of the cervical spine by the use of head/shoulder and mouth grip. To compare degenerative changes in the cervical spine in TE individuals with healthy controls (CTR). Twenty-seven middle-aged TE individuals and 27 age- and gender-matched CTR were examined by cervical spine MRI. The presence of malformations, disc herniation(s), osteophytes, nerve and medullary compression and the degree of disc degeneration (DD) were evaluated. Significantly higher degree of DD was seen in the TE group compared with the controls (p<0.001). Similar frequencies of disc herniation and disc space narrowing were observed in the two groups, but more foraminal narrowing was seen in the TE group (p = 0.002). DD was observed relatively frequently at all cervical levels in the TE group, however, mainly at the two lower levels in the CTR. Middle-aged individuals with TE have a higher frequency of degenerative changes in the cervical spine than controls, possibly caused by an altered load on the cervical spine.